Gestão pedagógica na educação a distância: análise de uma experiência na perspectiva da gestora - Cerny, Roseli Zen (2009)
The present study attempts to analyze a pedagogical management system developed in a public institution of higher education during the implementing of one of the first distance education licentiate courses. The theoretic principals are based on the referential management of educational systems and the perspective of distance education systems. A qualitative methodology was utilized for this research, with the support of the enunciation theory of language and the method of self observation. The pedagogical management system was created based on the idea of collaborative work and anchors itself on the triad formation, materials production and research and evaluation. In the analysis of the distance education system it became clear that the main difficulties for the implementation of undergraduate courses are: the history of distance education in the institution, the culture of presence, the somewhat inflexible model of institutional organizations, the way by which financing is decentralized and administrated, the public and bureaucracy politics. In the organization of the teams there is the perception that the pedagogical management reproduces in part the presential model referring to the partnership between the centers of teacher formation. The study illustrates that the formation of the teams constitutes a privileged space for minimizing the prejudice against this modality of learning, promoting the integration between members, rethinking the didactic pedagogical action and providing reception to team members. Research and evaluation are pointed out as decisive conditions for the university s participation in distance education, aiding the partnership between centers. It has been made evident that the collective construction of work demands time and openness by part of teams for new constructions to arise. It is possible to conclude that, even with the tensions and troubles lived in this proposal of pedagogical management, the integrated work of formation, material productions and research and evaluation contribute to a more organic performance in distance education, breaking the fordist paradigms found normally in the experiments with this modality of learning